Lietuvos Valstybės Prezidento kalbų ir Tautos šventės iškilmių sąveika (1920-1938): poveikio komunikacija - Ulytė-Grigelevičienė, Vita (Lietuvos istorijos studijos, 2009)
The present article discusses distinctive aspects of the National Day (Tautos šventė) celebrations, which were aimed at the general public, in Lithuania in the period between 1920 and 1938 and the form and content of the speeches delivered by the President of State during these celebrations in order to make a strategic impact on the citizens. With the aim of examining the character of these phenomena, the research focuses on the aspect of influential communication. The research presented in the article has been carried out using the methods of statistical/contrastive analysis and rhetorical analysis. The analysis of the subject starts with a brief overview of the origins and process of the National Day in Lithuania and the examination of its distinctive aspects. The objective of this part of the analysis is to determine the main reason for the existence of the National Day in Lithuania. The article further examines the reaction of the National Day celebration participants to the public appearance of the President of State and explores the features of the impact strategy revealed by the President's opening speech made on the occasion of the celebration. The research aims at reconstructing the overall pattern of influential communication, which was reflected in the connection between the President of State and the crowds of general public at that time.So far, similar analyses attempting to reveal the problem of influential communication have only rarely been encountered in the works of Lithuanian historians or have only touched upon the subject. Therefore, the main sources on the basis of which the subject of the article is examined are periodicals (mainly newspapers) of the period under consideration. These publications contain quite exhaustive texts on both the National Day celebrations (its programmes and impressions) and the speeches made by the President (the exact texts of the speeches or paraphrased speeches).The article suggests and attempts to prove the hypothesis that the sender of a political speech strategically constructs the impact directed towards receivers of the speech. This approach is confirmed by the main conclusion of the article, which proves that both the fragments of Lithuania's National Day celebrations of the period between 1920 and 1938 and the President's speeches addressed to the general public were strategically constructed as influential communication. Celebrations of the National Day manifest a sort of a "warming up" moment of impact based on the elements of visual effect, which enhanced positive spirits among the public and in turn strengthened the effect of the President's speeches, thus enabling them to achieve the intended purposes. On the other hand, the strategy process, which disclosed the verbal effect and determined three main aspects of the President's speeches: firstly, the development of the patriotic arguments to enhance the feelings of dignity and honour and their substantiation; secondly, the use of terms encouraging enthusiasm and inspirational expressions; and thirdly, the use of figures of speech to evoke the spirit of community and solidarity, was not only constructed to charge the public ideologically but also aimed at making an emotional impact on the minds of the public, thus gaining control over the people's will.